Awareness of COVID-19 outbreak in local population of Maval taluka in Maharashtra, India - Pratinidhi, Shilpa A.; Sayyed, Anjum A. K.; Tilokchandani, Mohak A.; Malode, Sudnya V.; Bhalgat, Siddhi S.; Bhujbal, Chaitanya R. (International Journal of Research in Medical Sciences, 2020)
Background: There is a growing fear and perceived threat about coronavirus among local population. The population, inclusive of all age groups is making use of available media such as internet, social media, newspapers and television to make themselves aware. There is no authenticity and information may be wrong. Since, corona has become major cause of concern, present study was carried out to bring the awareness and educate them about coronavirus among the local population. Methods: A cross sectional study was carried out on COVID-19 by using online Google based questionnaire in Maval area to assess the knowledge and awareness about corona virus among the 125 local participants. The questionnaire consisted of 10 validated peer reviewed questions covering various aspects of COVID-19 awareness were voluntarily filled by participants. Data was analysed in Microsoft Excel 2010. Results: Present findings revealed that 94% participants knew that COVID-19 is caused by the corona was first detected in Wuhan China and the first case of the same was reported in Kerala was known to 60% respondents. The virus remains on the surface of mobiles was known to 11% participants.76.8% participants apprised 2-14 days being the incubation period of the virus. Patients with two or more comorbidities can develop severe COVID-19 was known to 46.6% participants. Only 5% participants knew the difference between swine flu and corona virus. Nearly 89% participants knew soap is the best material for cleaning in the presence of dirt and about 51% participants knew the need of isolating persons with known COVID- 19 infection. Conclusions: Correct answers with scientific explanation were posted to the participants in the form of instantaneous feedback. Hence knowledge gained was increased by the participants. Their misconceptions were removed. More awareness can be brought & propagation of COVID-19 infection can be prevented even after lockdown period.